Tribocorrosion Behavior of Micro/Nanoscale Surface Coatings - Md Ashraful Hoque; Chun-Wei Yao; Mukunda Khanal; Ian Lian (Sensors, 2022)
Wear and corrosion are common issues of material degradation and failure in industrial appliances. Wear is a damaging process that can impact surface contacts and, more specifically, can cause the loss and distortion of material from a surface because of the contacting object’s mechanical action via motion. More wear occurs during the process of corrosion, in which oxide particles or debris are released from the contacting material. These types of wear debris and accumulated oxide particles released during corrosion cause a combination of wear-corrosion processes. Bringing together the fields of tribology and corrosion research, tribocorrosion is a field of study which deals with mechanical and electrochemical interactions between bodies in motion. More specifically, it is the study of mechanisms caused by the combined effects of mechanical stress and chemical/electrochemical interactions with the environment. Tribocorrosion testing methods provide new opportunities for studying the electrochemical nature of corrosion combined with mechanical loading to establish a synergistic relationship between corrosion and wear. To improve tribological, mechanical, and anti-corrosion performances, several surface modification techniques are being applied to develop functional coatings with micro/nano features. This review of the literature explores recent and enlightening research into the tribocorrosive properties of micro/nano coatings. It also looks at recent discussions of the most common experimental methods and some newer, promising experimental methods in tribocorrosion to elucidate their applications in the field of micro/nano coatings.